The complete mitochondrial genome of the widely cultivated edible fungus Lentinula edodes. Issue 1 (1st January 2017) - Yang, Ruiheng; Li, Yan; Song, Xiaoxia; Tang, Lihua; Li, Chuanhua; Tan, Qi; Bao, Dapeng
Abstract: The complete mitochondrial genome of the widely cultivated edible fungus Lentinula edodes was determined using the next-generation sequencing technology. The circular molecule is 116, 819 bp in length with a GC content of 30.75%. Conserved genes including 13 putative protein-coding genes and 24 tRNAs were located on the same strand. We detected 14 introns invading 4 genes, including cob, cox1, nad1, and nad5. The phylogenetic analysis confirmed that L. edodes was a number of Agaricales. This mitochondrial genome may open new avenues for understanding the phylogeny and evolution of Omphalotaceae and Agaricales.